Writing an inheritance : women's writing in Sri Lanka, 1860-1948 - De Mel, Neloufer; Samarakkody, Minoli; Gooneratne, Yasmine, 1935-; Women's Education and Research Centre (Colombo, Sri Lanka) (Colombo : Women's Education & Research Centre, 2002)
Chiefly collection of literary writtings.
V. 2 edited by Yasmine Gooneratne.
Keywords: Sri Lankan literature (English) -- Women authors